PENERAPAN CONCEPTUAL CHANGE TEXT BERBANTUAN PHET SIMULATION UNTUK MEREMEDIASI MISKONSEPSI FLUIDA DINAMIS DI SMA - Dwidianti, Bintari; Sahala S, Stepanus; ., Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractIn this study, the effect of conceptual change text (CCT) with PhET simulation to remediate students? misconceptions of fluid dynamic at SMA was investigated. Quasi-experimental with non-equivalent control group design was used which involved 62 eleventh grade students. This study was made of into two groups. Experimental group (N=29) were given CCT with PhET simulation, whereas the control group (N=33) were given re-test. Nine open-ended multiple-choice questions concerning fluid dynamic were used as data collection tool. The results showed experimental group?s average of decreasing students? misconceptions (59,58%) were higher than control group (15,57%), and caused differences between both of groups that were proved by two-sample proportions test, Zscore (2,08) > Ztable (1,96). In the other hand, decreasing quantity of that misconception (DQM) value showed CCT with PhET simulation more effective than re-test to remediate students? misconceptions about fluid dynamic. It determined that CCT with PhET simulation could be alternative to remediate students? misconceptions. Keyword: Remediate, Misconception, CCT, PhET Simulation, Fluid Dynamic